Aspirin and the risk of cardiovascular events in atherosclerosis patients with and without prior ischemic events. Issue 9 (18th May 2017) - Bavry, Anthony A.; Elgendy, Islam Y.; Elbez, Yedid; Mahmoud, Ahmed N.; Sorbets, Emmanuel; Steg, Philippe Gabriel; Bhatt, Deepak L.; ,
Abstract : Background: The benefit of aspirin among patients with stable atherosclerosis without a prior ischemic event is not well defined. Hypothesis: Aspirin would be of benefit in outpatients with atherosclerosis with prior ischemic events, but not in those without ischemic events. Methods: Subjects from the Reduction of Atherothrombosis for Continued Health registry were divided according to prior ischemic event (n =21 724) vs stable atherosclerosis, but no prior ischemic event (n = 11 872). Analyses were propensity score matched. Aspirin use was updated at each clinic visit and considered as a time‐varying covariate. The primary outcome was the first occurrence of cardiovascular death, myocardial infarction, or stroke. Results: In the group with a prior ischemic event, aspirin use was associated with a marginally lower risk of the primary outcome at a median of 41 months (hazard ratio [HR]: 0.81, 95% confidence interval [CI]: 0.65‐1.01, P = 0.06). In the group without a prior ischemic event, aspirin use was not associated with a lower risk of the primary outcome at a median of 36 months (HR: 1.03, 95% CI: 0.73‐1.45, P = 0.86). Conclusions: In this observational analysis of outpatients with stable atherosclerosis, aspirin was marginally beneficial among patients with a prior ischemic event; however, there was no apparent benefit among those with no prior ischemic event.